2007
DOI: 10.1016/j.yexcr.2007.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackie and adenovirus receptor (CAR) is a product of Sertoli and germ cells in rat testes which is localized at the Sertoli–Sertoli and Sertoli–germ cell interface

Abstract: The coxsackie and adenovirus receptor (CAR), a putative cell-cell adhesion molecule, has attracted wide interest due to its importance in viral pathogenesis and in mediating adenoviral gene delivery. However, the distribution pattern and physiological function of CAR in the testis is still not clear. Here, we identified CAR in Sertoli cells and germ cells of rats. In vivo studies have shown that CAR resides at the blood-testis barrier as well as at the ectoplasmic specialization. The persistent expression of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 56 publications
3
61
0
Order By: Relevance
“…2A). It is worth noting that previous studies have shown all of these proteins to localize to the Sertoli cell barrier/BTB (Cheng and Mruk, 2012;Cyr et al, 1999;Hellani et al, 2000;Mruk and Cheng, 2004;Su et al, 2010a;Wang et al, 2007;Wong et al, 2004). To validate that ICAM-1 was indeed a constituent protein of the BTB, Sertoli cells (previously cultured for 4 days and having a functional barrier that mimicked the BTB in vivo) were fluorescently immunostained and analyzed by confocal microscopy (Fig.…”
Section: Icam-1 Is An Integral Component Of the Btbmentioning
confidence: 98%
“…2A). It is worth noting that previous studies have shown all of these proteins to localize to the Sertoli cell barrier/BTB (Cheng and Mruk, 2012;Cyr et al, 1999;Hellani et al, 2000;Mruk and Cheng, 2004;Su et al, 2010a;Wang et al, 2007;Wong et al, 2004). To validate that ICAM-1 was indeed a constituent protein of the BTB, Sertoli cells (previously cultured for 4 days and having a functional barrier that mimicked the BTB in vivo) were fluorescently immunostained and analyzed by confocal microscopy (Fig.…”
Section: Icam-1 Is An Integral Component Of the Btbmentioning
confidence: 98%
“…In recent years, some of the proteins that are known to be confined to cell-matrix interface at the focal contact (also known as focal adhesion complex, an actin-based cell-matrix anchoring junction type) to facilitate cell movement were found to be components of the apical ES, such as FAK, ILK (integrin-linked kinase) and vinculin. [16][17][18] Additionally, gap junction proteins (e.g., connexin 43,19 ) and tight junction proteins (e.g., JAM-C, junctional adhesion molecule-C also known as JAM-1), 20 coxsackie and adenovirus receptor (CAR), 21,22 are also found to be integrated components of the apical ES, making it a hybrid anchoring junction type. 4,8,15,23 However, a detailed analysis on the components of the integrin-based cell adhesion protein complex which regulate signaling function at the apical at 2 d (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Germ cell movement across the seminiferous epithelium during spermatogenesis is associated with extensive junction restructuring [4][5][6][7][8], including dynamic changes in the BTB [2,9,10,[35][36][37]. As shown in Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The BTB is a dynamic structure that undergoes cycles of "opening" and "closing" during the epithelial cycle to facilitate germ cell migration, yet its integrity must not be compromised in order to maintain the microenvironment behind it. On the other hand, recent advances concerning the molecular architecture of the BTB have shifted attention to understanding some of the key events that regulate spermatogenesis, such as opening and closing of the BTB to permit timely passage of primary spermatocytes across the it [4][5][6][7][8][35][36][37]. The results of recent research in this area also suggest that the BTB in the seminiferous epithelium must "open" to accommodate migration of primary spermatocytes from the basal compartment to the adluminal compartment.…”
mentioning
confidence: 99%